2020
DOI: 10.1007/s00521-020-05101-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene encoder: a feature selection technique through unsupervised deep learning-based clustering for large gene expression data

Abstract: Cancer is a severe condition of uncontrolled cell division that results in a tumor formation that spreads to other tissues of the body. Therefore, the development of new medication and treatment methods for this is in demand. Classification of microarray data plays a vital role in handling such situations. The relevant gene selection is an important step for the classification of microarray data. This work presents gene-encoder, an unsupervised two-stage feature selection technique for the cancer samples' clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Pseudo-Guided Multi-Objective Genetic Algorithm (PGMOGA) proposed that reconstitutes pathways by assigning orientation weighted network edges (Iqbal & Halim, 2020). A gene encoder presented that incorporates twostage feature selection with an unsupervised type for the classification of cancer samples (Al-Obeidat et al, 2020). There is a requirement of finding the correct DNA sequence to get the desired information about the genetic makeup of an organism.…”
Section: Anemia and Sickle Cell Detectionmentioning
confidence: 99%
“…Pseudo-Guided Multi-Objective Genetic Algorithm (PGMOGA) proposed that reconstitutes pathways by assigning orientation weighted network edges (Iqbal & Halim, 2020). A gene encoder presented that incorporates twostage feature selection with an unsupervised type for the classification of cancer samples (Al-Obeidat et al, 2020). There is a requirement of finding the correct DNA sequence to get the desired information about the genetic makeup of an organism.…”
Section: Anemia and Sickle Cell Detectionmentioning
confidence: 99%
“…Zhang et al [51,52] introduce a parallel architecture of a convolutional neural network and a recurrent neural network. The joint output of both the networks is then fed to an autoencoder layer [32,43] to learn a compressed and distributed representation of EEG features. For classification, Extreme Gradient Boosting (XGBoost) classifier is used.…”
Section: Past Work Summarymentioning
confidence: 99%
“…In healthcare area, GA was utilized to improve the classification models by finding the optimum feature subsets for gene encoder, hepatitis prediction, and COVID-19 patients' detection. Uzma et al (2020) proposed gene encoder based on GA to evaluate the feature subset and three machine learning models such as support vector machine (SVM), k-nearest neighbors (KNN), and random forest (RF) were used to classify the cancer samples [29]. The experiments on six benchmark datasets revealed that GA-based feature selection improved the performance of all models used in their study.…”
Section: Extreme Gradient Boosting (Xgboost) and Genetic Algorithms (Ga)mentioning
confidence: 99%
“…Genetic algorithms (GAs) have been previously used for feature selection and showed significant results for selecting the best feature sets [24,25]. In the health arena, GA can highly improve the performance of models for emotional stress state detection [26], severe chronic disorders of consciousness prediction [27], children's activity recognition and classification [28], gene encoder [29], hepatitis prediction [30], and COVID-19 patient detection [31].…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 99%
See 1 more Smart Citation